Cardiac Cephalgia: Angina in the Head (Bangladesh Medical Journal, 2021)
Cardiac cephalgia is a migraine like headache that occurs during episodes of myocardial ischaemia. Although most of the patients presenting with ischaemic heart disease have chest pain, there are other rare presenting symptoms like cardiac cephalgia. Headache can be the only presentation of coronary artery disease. We report a case of a 57 years-old man, Presenting with only headache during brisk walking, Exercise Tolerance Test (ETT) was positive for Electrocardiograph (ECG) evidence of provocable myocardial ischemia, who latter was diagnosed as double vessel coronary artery diseaseon Coronary Angiogram (CAG). As the patient preferred remaining without revascularization, he was put onto optimum medical management for ischaemic heart disease. A follow up visit after one month revealed, marked improvement of the headache with anti anginal medications. Early evaluation and diagnosis of the headache symptom should be done because treatment with anti-migraine drugs may deteriorate headache and undermine the diagnosis of coronary artery disease.Bangladesh Med J. 2019 Sep; 48 (3): 46-49